El Código Civil peruano de 1984: Su elaboración, sus aportes, las enmiendas que reclama - Fernández Sessarego, Carlos (Pontificia Universidad Católica del Perú, 2014)
In 1965 a Reforming Committee, formed by the leading specialist teachers in each of the books of the Civil Code, was created forreviewing  the  Peruvian  Civil  Code of 1936. After about twenty years, the effort of thehard work of the committee resulted in the enactment of the 1984 Civil Code, which we currently use and know.In this article, the author shares his experience as a legislator, emphasizing new and important aspects included in the Civil Code of 1984. He also proposes possible amendments to the First Book of the current Civil Code, such as the incorporation of standards related to Genetics, a comprehensive review of the subject related to legal capacity, reviewing the subject regarding foundations, among others.

En 1965, se creó una Comisión Reformadora, conformada por los más destacados profesores especialistas en cada uno de los libros quecomponen el Código Civil, encargada de revisar el Código Civil peruano de 1936. Después de aproximadamente veinte años, el esfuerzodel arduo trabajo de la Comisión dio como resultado la promulgación del Código Civil de1984, que actualmente conocemos y usamos.En el presente artículo, el autor nos cuenta su experiencia como legislador, haciendo énfasis en los nuevos aspectos incorporados y la importancia de la promulgación del Código de 1984. Asimismo, propone posibles enmiendas al Libro I del Código actual, tales como la incorporación de normas relacionadas con la Genética, la revisión integral de la temática referente a la capacidad jurídica, la revisiónde la temática sobre fundación, entre otras.
The 1984 Peruvian Civil Code: Its elaboration, contributions and the amendments it requires
Keywords: Law; Reforming Committee; Law Of Persons; Legal Capacity; Legal Entity; Amendment; Comisión reformadora; Derecho de personas; Capacidad jurídica; Persona jurídica; Enmienda; https://purl.org/pe-repo/ocde/ford#5.05.01